2019
DOI: 10.1038/s41467-019-10108-0
|View full text |Cite
|
Sign up to set email alerts
|

Local membrane charge regulates β2 adrenergic receptor coupling to Gi3

Abstract: The β 2 adrenergic receptor (β 2 AR) signals through both G s and G i in cardiac myocytes, and the G i pathway counteracts the G s pathway. However, G i coupling is much less efficient than G s coupling in most cell-based and biochemical assays, making it difficult to study β 2 AR−G i … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 73 publications
2
67
0
Order By: Relevance
“…5 compares the spectra of β 2 AR-G s EMPTY and β 2 AR-G i1 EMPTY complexes. Consistent with the previous observation that the β 2 AR-G i1 complex is less stable than the β 2 AR-G s complex ( 29 ), we observed smaller spectral changes in the β 2 AR-G i1 complex sample. The NMR spectral changes of K227 5.56 , K267 6.29 , K273 6.35 , and R328K 7.55 corresponding to the conformational changes of TM5, 6, and 7 are similar to those obtained from the β 2 AR-G s complex; however, peak 2 of K227 5.56 and K273 6.35 and peak 1 of K267 6.29 are notably weaker in the β 2 AR-G i1 complex compared to the β 2 AR-G s complex.…”
Section: Resultssupporting
confidence: 92%
“…5 compares the spectra of β 2 AR-G s EMPTY and β 2 AR-G i1 EMPTY complexes. Consistent with the previous observation that the β 2 AR-G i1 complex is less stable than the β 2 AR-G s complex ( 29 ), we observed smaller spectral changes in the β 2 AR-G i1 complex sample. The NMR spectral changes of K227 5.56 , K267 6.29 , K273 6.35 , and R328K 7.55 corresponding to the conformational changes of TM5, 6, and 7 are similar to those obtained from the β 2 AR-G s complex; however, peak 2 of K227 5.56 and K273 6.35 and peak 1 of K267 6.29 are notably weaker in the β 2 AR-G i1 complex compared to the β 2 AR-G s complex.…”
Section: Resultssupporting
confidence: 92%
“…This includes commonly used neutral detergents, as well as zwitterionic membrane lipids used in lipid nanodiscs or nanoparticles. With the ambition to mimic cellular membranes, it is reasonable to include negatively charged head groups in the membrane mimetic [ 88 , 89 ]. Ψ I comprises the electric potentials of the hydrocarbon core of the lipid membrane.…”
Section: Interactions Of Gpcrs With Their Membrane Environmentmentioning
confidence: 99%
“…PE, by contrast, favours an inactive receptor state. In a subsequent study, it was found that nanodiscs ApoA-1 POPC/POPG (3:2) and BPL/POPC/POPG (1.07:1.5:1) Ligand binding and G protein coupling of monomeric receptor (Kuszak et al 2009) Adenosine A 2A -receptor (A containing PG and PS headgroups modulate β 2 AR activation by the G s heterotrimer but surprisingly are inhibitory to β 2 AR activation by the G i3 heterotrimer in the absence of divalent cations (Strohman et al 2019). Instead, PE facilitates β 2 AR activation by G i3 , demonstrating that one type of lipid can exert different effects at the levels of GPCR conformation and GPCR-G protein coupling.…”
Section: Nanodiscsmentioning
confidence: 99%